EURO 2016 predictions using team rating systems - Lasek, J. (Machine Learning and Data Mining for Sports Analytics ECML/PKDD 2016 workshop, 2016)
In this study we employ several rating systems to generate predictions for the outcome of 2016 European Championships in association football. To this end, we first estimate probabilities of match results between all competing nations using the rating systems. Secondly, via Monte Carlo simulations we compute probabilities of advancing past a given stage of the tournament. The approach was developed for the Euro 2016 Prediction Competition organized within Sport Analytics Workshop at ECML/PKDD 2016